1988
DOI: 10.1002/1097-0142(19880715)62:2<355::aid-cncr2820620221>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and postoperative levels of plasma protein and amino acid in esophageal and lung cancer patients

Abstract: The metabolic changes following thoracic surgery in three groups of patients (esophageal cancer, lung cancer, and hiatus hernia) have been studied. Before operation patients with esophageal cancer, but not those with lung cancer, had significantly lower plasma total protein and albumin than patients with hiatus hernia. After surgery plasma albumin and total protein fell in both esophageal cancer and hiatus hernia patients, a development attributed to poor nutrition and restricted calorie diet in these two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 19 publications
1
24
1
Order By: Relevance
“…This study showed that tryptophan levels were significantly reduced in patients with esophageal cancer compared with controls (P ¼ 3.2EÀ0.5; fold change À1.2). This finding was supported by other groups, including Zhang and colleagues (21) and Naini and colleagues (33), who demonstrated decreased serum levels of tryptophan in these patients (Zhang VIP 3.35, P ¼ 0.000; Naini P < 0.05 for free tryptophan levels. Total tryptophan levels showed no significant change).…”
Section: Tryptophansupporting
confidence: 75%
“…This study showed that tryptophan levels were significantly reduced in patients with esophageal cancer compared with controls (P ¼ 3.2EÀ0.5; fold change À1.2). This finding was supported by other groups, including Zhang and colleagues (21) and Naini and colleagues (33), who demonstrated decreased serum levels of tryptophan in these patients (Zhang VIP 3.35, P ¼ 0.000; Naini P < 0.05 for free tryptophan levels. Total tryptophan levels showed no significant change).…”
Section: Tryptophansupporting
confidence: 75%
“…In previous studies, the alterations in PFAA profiles in cancer patients sometimes seem inconsistent, and some discrepancies existed between our study and those reported Lai et al, 2005;Naini et al, 1988;Norton et al, 1985;Proenza et al, 2003;Vissers et al, 2005). This discrepancy may be due not only to the statistical aspect of data, for example, sample size, the biased distribution of cancer stages, etc., but also to some other factors such as amino acid measurement methods.…”
Section: "Aminoindex Technology": Example For Early Cancer Diagnosiscontrasting
confidence: 84%
“…Several investigators have reported changes in plasma free amino acid (PFAA) profiles in cancer patients Lai et al, 2005;Lee et al, 2003;Maeda et al, 2010;Naini et al, 1988;Norton et al, 1985;Okamoto et al, 2009;Proenza et al, 2003;Vissers et al, 2005;Zhang & Pang, 1992). Despite evidence of a relationship between PFAA profiles and some types of cancer, few studies have explored the use of PFAA profiles for diagnosis because although PFAA profiles differ significantly between patients, the differences in individual amino acids do not always provide sufficient discrimination abilities by themselves Lai et al, 2005;Naini et al, 1988;Norton et al, 1985;Proenza et al, 2003;Vissers et al, 2005).…”
Section: "Aminoindex Technology": Example For Early Cancer Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In a study in rats, we observed a reduced blood flow to the small intestine when plasma concentrations of arginine were low in the presence of low-grade endotoxemia (Prins et al, 2000a). Circulating arginine is reduced in a number of clinical conditions, for example, after thoracoabdominal aortic surgery (Nijveldt et al, 2000), after surgery for esophageal and lung cancer (Naini et al, 1988), after trauma (Houdijk et al, 1998), during sepsis (Freund et al, 1978), and in severe burns (Yu et al, 1995). Because of the many physiological functions of arginine, low levels of this amino acid may be related to the high morbidity and mortality rates in these patient groups.…”
Section: Introductionmentioning
confidence: 98%